The Collection Svinja je odličan plivač (1971) by Miroljub Todorović in the Light of Serbo-Polish Connections - Marićević Balać, Jelena (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The introductory part of the paper highlights the threefold importance of Miroljub Todorović’s poetry collection Svinja je odličan plivač [A Pig Is an Excellent Swimmer] (1971). The success of the book is important for Signalism and the work of Miroljub Todorović, as well as literary reception since a selection of his poetry (2009) and a recent Polish edition (2020) bear the same title. We refer to the image of the pig as in a diary and the poetry and prose in Šatrovački argot, so as to portray the poetic pig motif as complementary with the works of Signalism. Ultimately, we approach the 1971 poetry collection in a comparatist manner, comparing the poetry of Signalism to the poetry of the Polish poetess Ewa Lipska. In relation to being compared to the poetry of Ewa Lipska, the pig becomes a signum of a mankind deprived of love. Further comparison between the poetry book Svinja je odličan plivač and the poetry of the Polish poetess is founded on the similarities and differences in terms of their respective relationship towards machines, surrealism, the eyes motif, children, the concept of time, and the figures of Shakespeare and Socrates.
Keywords: signalism; reception; the pig motif; Miroljub Todorović; Ewa Lipska